Term premium in emerging market sovereign yields: Role of common and country specific factors - İbrahim Özbek; İrem Talaslı (Central Bank Review (CBR), 2020)
This paper provides cross-country analysis of local bond market term premia in emerging countries. In order to investigate the role of domestic and global factors in the determination of compensation demanded by investors for their medium and long term fixed income investments, term premia is computed for emerging countries by using methodology adopted in Adrian et al. (2013). It is found that changes in market liquidity conditions is important for the variation in term premia. Moreover, movements in domestic and global factors are closely linked to term premia. In this regard, uncertainty related economic surprise indicator and exchange rate related expectations subsume some part of the expected excess returns in both medium and long term. Among other explanatory variables, inflation uncertainty is the only variable found to be insignificant in medium term, albeit it has an explaining power in the long term.
Keywords: G10; G11; G15; 330; Panel regression; Risk-neutral yields; Term premia; Yield curve